2021
DOI: 10.7554/elife.65545
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf open reading frame (DWORF) is a direct activator of the sarcoplasmic reticulum calcium pump SERCA

Abstract: The sarcoplasmic reticulum calcium pump SERCA plays a critical role in the contraction-relaxation cycle of muscle. In cardiac muscle, SERCA is regulated by the inhibitor phospholamban. A new regulator, dwarf open reading frame (DWORF), has been reported to displace phospholamban from SERCA. Here, we show that DWORF is a direct activator of SERCA, increasing its turnover rate in the absence of phospholamban. Measurement of in-cell calcium dynamics supports this observation and demonstrates that DWORF increases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 68 publications
8
61
0
Order By: Relevance
“…2H and I), consistent with enhanced DWORF-SERCA binding affinity at elevated cytoplasmic Ca 2+ (Fig. 2E) (4).…”
Section: Serca Affinity For Plb and Dworf Is Dependent On Ca 2+ -Pump Conformationsupporting
confidence: 77%
See 4 more Smart Citations
“…2H and I), consistent with enhanced DWORF-SERCA binding affinity at elevated cytoplasmic Ca 2+ (Fig. 2E) (4).…”
Section: Serca Affinity For Plb and Dworf Is Dependent On Ca 2+ -Pump Conformationsupporting
confidence: 77%
“…Importantly, PLB-SERCA complexes do not dissociate en masse during systole (Fig. 4D); we have previously reported that elevated Ca 2+ causes only small shifts in regulatory complex binding equilibria (4,22). Still, cardiac Ca 2+ transients simultaneously reduce PLB binding affinity and favor DWORF binding, driving a "dynamic fraction" of the population of these micropeptides to exchange from SERCA during each Ca 2+ transient.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations